(untitled) (Research, Society and Development, 2021)
The objective of this work was to evaluate the influence of temperature on the content of bioactive compounds of fruits of guabiju (Myrcianthes pungens (O. Berg) D. Legrand). The peel, pulp and seed of fresh guabiju were analyzed in relation to physical-chemical composition, metals, color, phenolic compounds, flavonoids, anthocyanins, vitamin C and antioxidant activity. On the dehydrated samples at temperature of 60 °C, where also determined the moisture and water activity. The fractions of the fruit showed high amounts of metals. After drying, moisture of 1.3, 1.0 and 0.9% were observed for peel, pulp and seed and water activity of 0.44 to 0.54. All the samples darkened, with less variation in the dehydrated peel (∆E 9.2). The samples showed high values of bioactive compounds, and in the fresh peel were observed higher levels of phenolic compounds (8459.8 mg EGA/100g dry extract), anthocyanins (152.0 mg/100 dry extract) and vitamin C (222.9 mg/100g) and on the dehydrated seed higher value of flavonoids (7480.7 mg EQ/100g dry extract). There was 86.3% degradation of anthocyanins in the dehydrated peel. The best values of antioxidant activities were obtained for the dehydrated peel (IC50 1.37 mg/mL), seed (IC50 1.49 mg/mL) and in the fresh peel (IC50 1.41 mg/mL).